Clinical Implications of Facial Edema in Chronic Mucormycosis: A Report of 5 Cases - Ángel, Josefina Alejandra Morales- Del; Morales-Chávez, Omar David; Méndez-Sáenz, Marco Antonio; Montemayor-Alatorre, Adolfo; Jasso-Ramírez, Nadia Gabriela; José, (Archives of Clinical and Medical Case Reports, 2020)
Objective: Describe 5 patients diagnosed with chronic mucormycosis who presented facial edema as initial symptom. Method: Retrospective study of 5 patients, (3 men, 2 female) who came to the emergency room due to facial edema and nasosinusal symptoms that were diagnosed with chronic mucormycosis, a review of database clinical file was performed to describe their disease. The study was previously reviewed and approved by the University’s Ethics and Research Committees, receiving the registration number 0T18-00003. Results: In the 5 (100%) patients reported, we found a history of type 2 diabetes mellitus, with an average duration of facial symptoms of 3.7 months, characterized by intermittent facial edema accompanied by paresthesias, pain, and purulent rhinorrhea. In 3 (60%) patients we found necrotic lesions in middle turbinate and in 2 (40%) of them septal perforation. Mean glycemia and leukocytes at admission were 174.6 mg/dl and 7828 k/ul, respectively. The diagnosis was confirmed by histopathology with identification of hyphae compatible with the Mucoracea family. Conclusion: Chronic mucormycosis is a rare disease, associated to immunocompromised conditions. We can conclude that in patients with a history of uncontrolled diabetes mellitus, intermittent facial edema, and nasal symptoms for more than 4 weeks, it’s justified to perform a diagnostic approach for chronic mucormycosis.